(untitled) (Revista Iberoamericana de Bioética, 2025)
This article focuses on the bioethical and scientific analysis of euthanasia, with special attention to the Spanish case. The phenomenon of the possible slippery slope is addressed in those countries where it has been implemented within the framework of a global comparison that allows us to establish synonymous guidelines and synergies in the different places since its development. The analysis has been worked from original sources that allow us to collect the latest data.